Recent Progression Of Chromium And Its Salts For Combating In Kinds Of Human Metabolic Disorder And Diseases (Journal of Namibian Studies : History Politics Culture, 2023)
Chromium is a glistening heavy metal that found in rocks, volcanic dust and gases, soil, animal and plants. Generally metallic chromium is mined to use in metal and steel industry.In veggies, barley, fruit, fish and meat little chromium is found. The hexavalent form of chromium is toxic, causing mutation and cancer. Other chromium salts like trivalent, chloride, acetate, chromium nicotinate, chromium picolinate, chromium polynicotinate, chromium proteinate, trichloride and tripicolinate is being used in various human disease. Chromium is a vital mineral that seems to have a positive impact in the control of insulin, metabolism and cardiovascular disease also protect against injury to the liver. In a recent study the content of pro inflammatory cytokines (IL-12, TNF-α and IL-1β) has decreased by chromium and control values in the animal model for hepatic steatosis which recovered the anti-inflammatory cytokine (IL-10) values. Chromium has proven anti-inflammatory capabilities in our prior investigation in diabetic patients. Chromium has proven to improve the susceptibility of insulin in type II diabetes. Chromium supplementation also reduced liver damage in rats of chronic cholestasis. In future chromium would be the metal of choice in combating various human diseases after the study of therapeutic dosages and clinical trials.